Analysis of the Learning Process in High School During the Covid-19 Pandemic: Case Study in Palu City - Normawati, Normawati; Mansur, Mansur (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
during the COVID-19 pandemic. The author conducts a case study of Palu City high school students (SMA). The government has set limits on human mobility to halt the development of the COVID-19 pandemic, which could negatively impact the learning process of students. The COVID-19 pandemic affects kids' educational process, which students in Palu City are also experiencing. Learning occurs both offline and online during the COVID-19 pandemic. This relates to the government's policy on learning during the COVID-19 pandemic. This study employs a qualitative technique in conjunction with a literature review. The author draws on secondary data sources from 25 national journal articles published between 2019 and 2021 to examine the techniques and patterns of learning during the COVID-19 pandemic. The findings of this study indicate that: 1) High school students in Palu City use the Blended Learning system to suit their learning demands during the pandemic by integrating offline and online platforms. 2) The Blended Learning approach has not been used to the full extent possible in the learning process of Palu City's high school pupils. 3) Students do not fully participate in the blended learning process. 4) Inadequate assistance resources available during the online learning process. 5) The practice of teaching high school pupils online through social media platforms such as WhatsApp (WA).